For all positive integers n , is 2 3 n + 1 always divisible by 3 n + 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are going to apply induction on n. For n = 0 the statement is obvious. Assuming that the claim is true for n consider the following:
2 3 n + 1 + 1 = ( 2 3 n ) 3 + 1 = ( 2 3 n + 1 ) ( 2 2 ⋅ 3 n − 2 3 n + 1 )
From 2 3 n + 1 ≡ 0 ( m o d 3 n + 1 ) and 2 2 ⋅ 3 n − 2 3 n + 1 ≡ 1 − 2 + 1 ≡ 0 ( m o d 3 ) (since 2 e v e n ≡ 1 and 2 o d d ≡ − 1 ( m o d 3 ) ) we conclude that 2 3 n + 1 + 1 ≡ 0 ( m o d 3 n + 2 ) . Hence our induction is complete.
For simplicity, we'll set 2 3 n + 1 = a n
Start of Induction: When n = 0 : 2 1 + 1 is divisible by 3 1
Inductive step: Since we have proven the statement for one n , we have to prove it for n + 1 , a n + 1 should be divisible by one more factor of 3 a n + 1 = 2 3 n + 1 + 1 = 2 3 ⋅ 3 n + 1 = ( 2 3 n ) 3 + 1 = ( 2 3 n ) 3 + 1 = ( 2 3 n + 1 − 1 ) 3 + 1 = ( a n − 1 ) 3 + 1 = a n 3 − 3 a n 2 + 3 a n − 1 + 1 = a n 3 − 3 a n 2 + 3 a n Since every part has at least one more factor of 3 than a n the whole sum has also one more factor of 3, making it divisible by 3 n + 2 □
Problem Loading...
Note Loading...
Set Loading...
2 3 n + 1 = ( 3 − 1 ) 3 n + 1 = k = 0 ∑ 3 n ( − 1 ) k ( k 3 n ) 3 3 n − k + 1 = k = 0 ∑ 3 n − 1 ( − 1 ) k ( k 3 n ) 3 3 n − k − 1 + 1 = k = 0 ∑ 3 n − 1 ( − 1 ) k ( k 3 n ) 3 3 n − k